O alinhamento entre a cultura organizacional e a utilização das práticas do modelo Cotec de gestão de tecnologia: um estudo em empresas do setor metal-mecânico da cidade de Ponta Grossa - PR - Prado, Jocimar Donizeti do (2009)
The present research concerns the matter of organizational culture in the effort made by companies to become technologically capable to succeed in a competitive environment, mainly aims to identify the key factors that must be present in the Organizational Culture for the deployment and efficient use of practice management technology proposed by Cotec Foundation for manufacturing companies in the metalmechanic sector in the region of Ponta Grossa - Pr. Therefore, it deals with matters relative to the conception of what an organizational culture is, drawing its main characteristics and what it is involved in the company decisions processes. It also analyses in details the Technology Management in Cotec model trying to determine the cultural elements present in it and the ones which come along with organization culture where it will be implemented. The method used to approach the problem is inductive focusing in the applied search. The research is classified as descriptive based in bibliographical references and a Field study. The data is in a predominantly quantitative but a qualitative analysis has been used in order to better understand the data obtained. The Field study was done in five important companies in mechanicalmetal section in Ponta Grossa - PR using two tools: a form and a survey, made through two instruments of research. Those tools intend to assess the level of knowledge and usage of the Cotec model practice and so to define a profile of organizational culture of each of the companies and the group of companies studied. As main results, the study show as some of the essential cultural elements for the operation of Cotec model and verified the existence of relations among these elements and the cultural profile detected in the organizations of the group studied. Among the elements identified, it was observed that the cultural positions related to the temporal focus of the organization, positioning in relation to the competitive environment, recovery of the hierarchy and form of reality testing are essential to the practice model Cotec can find suitable environment for its operation.